2010
DOI: 10.1039/b918648d
|View full text |Cite
|
Sign up to set email alerts
|

H/D exchange of molecular hydrogen with Brønsted acid sites of Zn- and Ga-modified zeolite BEA

Abstract: Kinetics of hydrogen H/D exchange between Brønsted acid sites of pure acid-form and Zn- or Ga-modified zeolites beta (BEA) and deuterated hydrogen (D(2)) has been studied by (1)H MAS NMR spectroscopy in situ within the temperature range of 383-548 K. A remarkable increase of the rate of the H/D exchange has been found for Zn- and Ga-modified zeolites compared to the pure acid-form zeolite. The rate of exchange for Zn-modified zeolite is one order of magnitude higher compared to the rate for Ga-modified zeolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
4
18
1
Order By: Relevance
“…They seem provide a similar acid strength as reported in literature. 51,52 A similar mobility (or line shape of 1 H MAS NMR) was observed with all H zeolites upon adsorption of CD3CN. Therefore, the small increase of Δd1H of the signal centers The acidity of H zeolites was also studied using NH3-TPD experiments.…”
Section: ◼ Results and Discussionsupporting
confidence: 55%
“…They seem provide a similar acid strength as reported in literature. 51,52 A similar mobility (or line shape of 1 H MAS NMR) was observed with all H zeolites upon adsorption of CD3CN. Therefore, the small increase of Δd1H of the signal centers The acidity of H zeolites was also studied using NH3-TPD experiments.…”
Section: ◼ Results and Discussionsupporting
confidence: 55%
“…A recent study on ZnO–ZrO 2 catalysts with different Zn/Zr ratios also suggested that the activation of H 2 on the catalyst with a higher Zn/Zr ratio was eaiser . Among different metal oxides, ZnO is well known for its ability to activate H 2 via heterolytic dissociation to form hydride (H – ) and proton (H + ) species. ,, The −Zn–O– domain in zeolite beta also facilitated H 2 activation as compared to the zeolite without zinc modification . The adsorbed hydride species could function for hydrogenation reactions including the hydrogenation of CO and CO 2 . ,, …”
Section: Resultsmentioning
confidence: 99%
“…72,74,75 The −Zn−O− domain in zeolite beta also facilitated H 2 activation as compared to the zeolite without zinc modification. 76 The adsorbed hydride species could function for hydrogenation reactions including the hydrogenation of CO and CO 2 . 70,72,77 To understand the remarkable difference in catalytic performances among MgAl 2 O 4 , ZnAl 2 O 4 , ZnGa 2 O 4 , and ZnCr 2 O 4 as well as the corresponding bifunctional catalysts for hydrogenation of CO and CO 2 (Tables 1 and 2), we have characterized these spinel oxides by EPR and H 2 −D 2 exchange reactions.…”
Section: Methodsmentioning
confidence: 99%
“…The Arrhenius plot in Figure yields the activation energy of 71 kJ mol –1 for a double-bond-shift reaction on the silicalite-1 sample activated at 673 K. A question arises whether this experimentally measured activation energy represents apparent ( E app ) or intrinsic ( E int ) activation barrier for the studied reaction. Most of the published works, concerning kinetic MAS NMR measurements in situ in a closed batch reactor, state that the method offers the values of apparent activation barriers. ,, ,,, However, no detailed discussion can be found in the literature to account for the effect of adsorption equilibrium in the closed NMR ampoules (a closed microreactor) on the experimentally measured activation energy. Indeed, 1 H MAS NMR is not often capable to resolve the signals of hydrocarbon molecules physisorbed on the surface of a catalyst and those in the gas phase, because the chemical shifts of the two states are close to each other or these states are averaged in the spectrum because of rapid exchange .…”
Section: Resultsmentioning
confidence: 99%